A Review on Factors Affecting Heat Transfer Efficiency of Nanofluids for Application in Plate Heat Exchanger - Haziqatulhanis, Ibrahim; Norazlianie, Sazali; Ahmad Syahiman, Mohd Shah; Mohamad Shaiful, Abdul Karim (Akademi Baru, 2019)
With the rapid advancement in science and technology, the enhancement in heat transfer is also making its way forward towards modern nanotechnology. It was noted that heat transfer efficacy of heat exchangers depends on the working fluid and nanofluid were discovered to enhance the heat transfer, making nanofluid our focus in this review. While shell and tube heat exchanger type were given attention since past decades, there are scarce on nanofluid application in plate heat exchanger. To add, thermophysical properties of nanofluids such as specific heat, viscosity, thermal conductivity and its heat transfer coefficient are very important for heat transfer application in heat exchangers. Therefore, this review article will cover the compilation of information and data collected from numerous previous researchers